Green Marketing vs. Green Marketing Greenwashing: A Narrative Review - Hasdiansa, Ilma Wulansari (Abadi Institute, 2025)
The food and beverage (F&B) industry in Indonesia has experienced rapid growth in recent years, yet it faces serious environmental sustainability challenges due to the waste and emissions it generates. Green marketing has emerged as an environmentally oriented marketing strategy to respond to consumer demand for eco-friendly products, whereas greenwashing represents a manipulative practice in which companies make misleading environmental claims for image purposes only. This study is a narrative review of literature published between 2021 and 2024 on green marketing versus greenwashing, with a focus on the Indonesian F&B industry. The review indicates that many Indonesian F&B firms have begun to adopt green marketing initiatives—such as the use of sustainable raw materials and recycled packaging—to build long-term competitive advantage. However, greenwashing is also increasingly prevalent, contributing to consumer skepticism and eroding trust in brands. Indonesian consumers are becoming more aware of environmental claims and demand greater transparency, with studies reporting that roughly one quarter of consumers distrust eco-friendly claims made by food brands. Prior research further shows that greenwashing practices negatively affect purchase intention and brand image by increasing skepticism and stimulating negative word of mouth, thereby strengthening calls for stricter regulation. To achieve long-term success, F&B companies must prioritize authentic green marketing and transparency over greenwashing; genuine commitment to sustainability can enhance consumer trust and competitiveness, whereas false green claims risk damaging reputation and customer relationships.